Economic Development in Communist China - Clark, Colin (Journal of Political Economy, 1976)
This text is an extension of a previous study, covering the period from the 1930s to 1959, published by the present writer in 1965. The results of the earlier study (amended) are included in the final table. Economic progress was violently interrupted by "The Year of the Great Leap Forward" (1958), when, as a result of misinformation about agricultural labor requirements and hysterically falsified statistics, it was claimed that agricultural output was being doubled in 1 year, and that immense transfers of labor to other employments were immediately possible. The result was acute agricultural shortages, indeed famine in 1960-61, and complete disruption of industrial production. Recovery from these disasters took several years. A lesser interruption (to industry but not to agriculture) took place in the "Cultural Revolution" of 1966-67. Those to whom the idea of a labor shortage in China appears paradoxical must be reminded that China has few draft animals and still fewer tractors. To cultivate a country the size of China with hand hoes requires several hundred million workers. Chinese population is probably substantially lower than is generally believed, and almost certainly has not been expanding at the rate of 2 percent per year frequently attributed to it. Famine conditions in the early 1960s caused a considerable reduction in the rate of population growth. Publication of Chinese official statistics virtually ceased in 1959, and sources of information for subsequent years are indirect and complex. The basis of the methods used is the construction of estimates of agricultural output and industrial production index numbers, supplemented by information about employment and wages. Almost all attempts hitherto to state China's (and other developing countries') national product in dollar terms give results considerably too low. The yuan has a high purchasing power over services and over some labor-intensive commodities. For a true comparison all Chinese consumption of food should also be revalued at U.S. retail prices. On this basis Chinese 1971 gross product per head, expressed in U.S. dollars of 1974 purchasing power, was 154 for food, 140 for other private consumption, and 157 for investment and government services, or 451 in all. The long-run rate of increase of real gross product per head of population has been about 2 percent per year, whether we take the 1930s or the early 1950s as our starting point. This rate is a little below the general average for developing countries, and much less than is usually claimed. Inequalities in income distribution in China are also not very different from those prevailing in other countries.